2022
DOI: 10.58996/hmj.v5i1.37
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Antibakteri Ekstrak Etanol Daun Alpukat (Persea americana Mill) Terhadap Escherichia coli, Salmonella typhi, dan Pseudomonas aeruginosa

Abstract: Infectious disease is a serious health problem in the world of health. Escherichia coli causes diarrhea, Salmonella typhi causes typhoid fever, and Pseudomonas aeruginosa causes nosocomial infections which are Gram-negative pathogenic bacteria. Treatment with antibiotics is the therapy that is currently used, but other efforts in the use of herbal medicines are also being carried out in various studies. The purpose of this study was to analyze the antibacterial activity of the ethanolic extract of avocado leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 7 publications
(9 reference statements)
0
10
0
1
Order By: Relevance
“…Positive bactericidal test findings were indicated by the creation of a clear zone surrounding the paper discs [20]. Figure 1 depicts the clean zone surrounding the paper discs in the antibacterial potential test of kemangi leaves extract.…”
Section: Antibacterial Potential Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Positive bactericidal test findings were indicated by the creation of a clear zone surrounding the paper discs [20]. Figure 1 depicts the clean zone surrounding the paper discs in the antibacterial potential test of kemangi leaves extract.…”
Section: Antibacterial Potential Resultsmentioning
confidence: 99%
“…The diameter of the inhibition zone for each concentration is shown in Table 3 for complete data.The results of the antibacterial test revealed that the bacterial inhibition zone at each concentration varied. This was attributable to the concentration differential, which also impacted the number of secondary metabolites present in each concentration [20]. The larger the zone of inhibition, the greater the concentration.…”
Section: Antibacterial Potential Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soaked for six hours, occasionally stirred, and then left to stand for eighteen hours. Next filtered once more, the filtering procedure was used, after which all of the macerate was collected and evaporated with a rotary evaporator to produce a thick extract [4].…”
Section: Preparation Of Ethanol Extract Solanum Mauritianum Scop Leavesmentioning
confidence: 99%
“…Erythromycin is one of the most popular antibiotics used to treat infections brought on by Staphylococcus aureus [3]. Pseudomonas aeruginosa is another bacterium that is similarly dangerous and pathogenic due to its amazing capacity to acquire new drug resistance as well as its virulence, or the ability of pathogenic bacteria to cause damage [4].An efficient and secure antibacterial agent that needs more research is needed to handle issues relating to bacterial infection.…”
Section: Introductionmentioning
confidence: 99%